Neutralizing activity of monoclonal antibodies to heat-sensitive and heat-resistant epitopes of Rickettsia rickettsii surface proteins. - Anacker, R L (1987)
Antiprotein monoclonal antibodies derived from mice inoculated with Rickettsia rickettsii heated at 56 degrees C for 15 min are of two types: one is type specific for epitopes denatured by moderate temperatures, and the other is specific for epitopes resistant to 100 degrees C for 5 min. The heat-resistant epitopes are found by immunoblotting on multiple polypeptides after solubilization of the rickettsiae at temperatures of 56 degrees C or higher. Most, but not all, antibodies to the heat-sensitive epitopes passively protected mice against two 50% lethal doses of R. rickettsii, whereas none of the antibodies to heat-resistant epitopes did.